Analisis Visual Pesan Dakwah dalam Kaligrafi Kontemporer di Instagram - Nuha, Achmad Arifulin; Sholeh, Moh. (Institut Agama Islam Syarifuddin Lumajang, 2024)
This study analyzes how contemporary calligraphy is used as a medium for Islamic preaching (dakwah) by Refil Andriansyah through the Instagram platform. Utilizing a qualitative approach with Charles Sanders Peirce's semiotic theory, this research examines the visual signs in Refil's works to understand the meanings embedded within them. The findings show that contemporary calligraphy not only serves as an aesthetic art form but also as an effective medium for spiritual communication. Symbols such as the